2021
DOI: 10.1128/mbio.00161-21
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae pv. phaseolicola Uses Distinct Modes of Stationary-Phase Persistence To Survive Bacteriocin and Streptomycin Treatments

Abstract: Antimicrobial treatment of bacteria often results in a small population of surviving tolerant cells, or persisters, that may contribute to recurrent infection. Antibiotic persisters are metabolically dormant, but the basis of their persistence in the presence of membrane-disrupting biological compounds is less well understood. We previously found that the model plant pathogen Pseudomonas syringae pv. phaseolicola 1448A (Pph) exhibits persistence to tailocin, a membrane-disrupting biocontrol compound with poten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…The apoplastic Flagella ON /T3SS OFF subpopulation is potentially more vulnerable to plant defenses since it elicits but cannot suppress immunity. We used propidium iodide to detect membrane-compromised (not viable) apoplast-extracted bacteria to determine if any of the phenotypic variants was subject to higher killing rates 35,36 . No significant differences were observed between the dead/live ratios of ON versus OFF subpopulations for either fliC , hrpL , hrcU or hopAB1 genes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The apoplastic Flagella ON /T3SS OFF subpopulation is potentially more vulnerable to plant defenses since it elicits but cannot suppress immunity. We used propidium iodide to detect membrane-compromised (not viable) apoplast-extracted bacteria to determine if any of the phenotypic variants was subject to higher killing rates 35,36 . No significant differences were observed between the dead/live ratios of ON versus OFF subpopulations for either fliC , hrpL , hrcU or hopAB1 genes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, unculturable cells that were considered to be in the VBNC state after the persistence state were analyzed by staining each individual cell according to its physiological characteristics. We were unable to get the five categories that Patel et al (2021) defined, because in this study, only two fluorescent dyes (the green vitality indicator RSG and red membrane permeability indicator PI) and one mixture fluorescence of them were used. Instead, we identified three classes ( Figure 2C ) and quadrant ( Supplementary Figure 3 ): class 1, redox-active cells with intact membranes being regarded VBNC cells in this experiment (green, Q4 in FITC-A image); class 2, which are redox-active cells with damaged membranes and considered to be true VBNC cells (yellow, Q2 in FITC-A image); class 3, redox-inactive cells with damaged membranes (red, Q1 in FITC-A image); and no defined class, unstaining cells (white, Q3 in FITC-A image).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in a few cases with copper ( Ordax et al, 2006 ) but not in a majority of cases with antibiotics, results of the fire blight pathogen E. amylovora varied by dormancy, including the induction of the persister and VBNC cells by chemical control agents. Recently, Patel et al (2021) reported that P. syringae pv. phaseolicola has the persistence to survive under streptomycin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported induction of viable but not culturable (VBNC) state and a concomitant alteration in the gene expression profile upon exposure of P. syringae cells to conditions that mimic oxidative burst of early stage plant infection ( Mock et al, 2015 ; Postnikova et al, 2015 ). We recently reported that a plant pathogenic P. syringae can survive bacteriocin and antibiotics exposure by entering another dormant, tolerant state known as persistence ( Kandel et al, 2020 ; Patel et al, 2021 ). Although several stress response pathways have been identified, it is still not well understood how P. syringae can cope with environmental stresses in epiphytic and free-living conditions or maintain virulence genes in the extended absence of host selection pressure.…”
Section: Introductionmentioning
confidence: 99%